Early diagnosis of neuropathy in leprosy--comparing diagnostic tests in a large prospective study (the INFIR cohort study). - Wim H van Brakel; Peter G Nicholls; Einar P Wilder-Smith; Loretta Das; Pramila Barkataki; Diana N J Lockwood (Public Library of Science (PLoS), 2008)
BACKGROUND: Leprosy is the most frequent treatable neuromuscular disease. Yet, every year, thousands of patients develop permanent peripheral nerve damage as a result of leprosy. Since early detection and treatment of neuropathy in leprosy has strong preventive potential, we conducted a cohort study to determine which test detects this neuropathy earliest. METHODS AND FINDINGS: One hundred and eighty-eight multibacillary (MB) leprosy patients were selected from a cohort of 303 and followed for 2 years after diagnosis. Nerve function was evaluated at each visit using nerve conduction (NC), quantitative thermal sensory testing and vibrometry, dynamometry, monofilament testing (MFT), and voluntary muscle testing (VMT). Study outcomes were sensory and motor impairment detected by MFT or VMT. Seventy-four of 188 patients (39%) had a reaction, neuritis, or new nerve function impairment (NFI) event during a 2-year follow-up. Sub-clinical neuropathy was extensive (20%-50%), even in patients who did not develop an outcome event. Sensory nerve action potential (SNAP) amplitudes, compound motor action potential (CMAP) velocities, and warm detection thresholds (WDT) were most frequently affected, with SNAP impairment frequencies ranging from 30% (median) to 69% (sural). Velocity was impaired in up to 43% of motor nerves. WDTs were more frequently affected than cold detection thresholds (29% versus 13%, ulnar nerve). Impairment of SNC and warm perception often preceded deterioration in MF or VMT scores by 12 weeks or more. CONCLUSIONS: A large proportion of leprosy patients have subclinical neuropathy that was not evident when only MFT and VMT were used. SNC was the most frequently and earliest affected test, closely followed by WDT. They are promising tests for improving early detection of neuropathy, as they often became abnormal 12 weeks or more before an abnormal monofilament test. Changes in MFT and VMT score mirrored changes in neurophysiology, confirming their validity as screening tests.